Effectiveness of Artemisia Vulgaris as Supplementation Against Chemotherapy of Mammae Adenocarcinoma to Reduce Expression of NF-ÎºB and CD 34 (Study in C3H Mice Given Chemotherapy Adriamycin - Cyclophosphamide) - Saputro, Bayu Teguh; Selamat Budijitno (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2021)
Intoduction: Breast cancer is a significant healthcare problem worldwide. Surgery remains the treatment of choice combined with other modalities such as chemotherapy, radiation, and immunotherapy such as Artemisia vulgaris (AV). Selective cytotoxicity of AV is intended as a supplementation to Adriamycin-Cyclophosphamide, improving the response rate of chemotherapy in adenocarcinoma mammae. Method: This study used a